Integrative Reconstruction of Islamic Education Learning Model to Enhance Values in Madrasah Ibtidaiyah - Siti Husnul Khatimah; Sabarudin Sabarudin; Fira Nur Anisa; Putri Lizah Aryani; Mutia Miftachul Jannah (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study examines the reconstruction of an Islamic Education learning model based on integration–interconnection in an Islamic elementary school. Using a qualitative case study approach, the research involved school principals, Islamic Education teachers, general subject teachers, and students. Data were collected through participatory observation, semi-structured interviews, and documentation of instructional materials. Thematic analysis followed Miles and Huberman’s framework, encompassing data condensation, presentation, and conclusion drawing, with validity ensured through triangulation of sources, techniques, and time. Findings indicate that integration–interconnection functions as both a conceptual and epistemological foundation, positioning Islamic Education as the core value permeating interdisciplinary learning. The reconstructed pedagogical design emphasizes value habituation, teacher exemplification, reinforcement of religious and social practices, and integrative teaching materials linking Islamic Education with science, social studies, and health. This model contributes to holistic internalization of Islamic values across cognitive, affective, and psychomotor domains, fostering moderate religious character among students. Nevertheless, implementation faces challenges such as dual curriculum administrative burdens, limited family support, and diverse student backgrounds. The cultural context of Nahdlatul Ulama provides strong cultural capital that sustains value-based education.